Notch1 and Notch2 receptors regulate mouse and human gastric antral epithelial cell homoeostasis. Issue 6 (1st March 2016) - Gifford, Gail B; Demitrack, Elise S; Keeley, Theresa M; Tam, Andrew; La Cunza, Nilsa; Dedhia, Priya H; Spence, Jason R; Simeone, Diane M; Saotome, Ichiko; Louvi, Angeliki; Siebel, Christian W; Samuelson, Linda C
Abstract : Objective: We tested the ability of Notch pathway receptors Notch1 and Notch2 to regulate stem and epithelial cell homoeostasis in mouse and human gastric antral tissue. Design: Mice were treated with the pan-Notch inhibitor dibenzazepine (DBZ) or inhibitory antibodies targeting Notch1 and/or Notch2. Epithelial proliferation, apoptosis and cellular differentiation were measured by histological and molecular approaches. Organoids were established from mouse and human antral glands; growth and differentiation were measured after treatment with Notch inhibitors. Results: Notch1 and Notch2 are the predominant Notch receptors expressed in mouse and human antral tissue and organoid cultures. Combined inhibition of Notch1 and Notch2 in adult mice led to decreased epithelial cell proliferation, including reduced proliferation of LGR5 stem cells, and increased apoptosis, similar to the response to global Notch inhibition with DBZ. Less pronounced effects were observed after inhibition of individual receptors. Notch pathway inhibition with DBZ or combined inhibition of Notch1 and Notch2 led to increased differentiation of all gastric antral lineages, with remodelling of cells to express secretory products normally associated with other regions of the GI tract, including intestine. Analysis of mouse and human organoids showed that Notch signalling through Notch1 and Notch2 is intrinsic to the epithelium and required for organoid growth. Conclusions: Notch signalling is required to maintain gastric antral stem cells. Notch1 and Notch2 are the primary Notch receptors regulating epithelial cell homoeostasis in mouse and human stomach.